Dog poems - Livingston, Myra Cohn; Morrill, Leslie (Oxford Unversity Press, 1990)
From new-born puppies to old hounds, the poems in this book describe all kinds of dog. There are big dogs and small dogs, pedigree and mongrels - hunting, playing, chasing cats, and burying bones. Traditional and new poems combine in this celebration of man's best friend.